Validity and Practicality of Hydrocarbon LKPD Based on Guided Inquiry Learning (GIL) Integrated with Ethnoscience for Phase F SMA/MA - Rahminawati, Rahminawati; Andromeda, Andromeda (FKIP - Universitas Riau, 2025)
The advancement of time and technology has resulted in foreign cultures easily entering, which can displace students' knowledge of cultural values. This poses a challenge for educators to develop ethnoscience-integrated teaching materials. The purpose of this research is to produce Hydrocarbon LKPD Based on Guided Inquiry Learning Integrated with Ethnoscience for Phase F SMA/MA. The type of research used is educational design research, employing the Plomp model. This research was conducted by designing LKPD, which was followed by the validation and practicality stages. The research instruments used are the validity questionnaire and the practicality questionnaire. The validity questionnaire was analyzed using the Aiken’s V formula, while the practicality questionnaire was analyzed using the percentage method. The validity test results yielded an average of 0.85, which falls into the valid category, while the practicality questionnaire results showed a score of 92% from student responses and 91% from teacher responses, both categorized as very practical. Based on the research results, it can be concluded that the hydrocarbon LKPD based on guided inquiry learning integrated with ethnoscience for Phase F SMA/MA is declared valid and practical, thus can be used in the learning process.